2018
DOI: 10.1016/j.chiabu.2018.03.029
|View full text |Cite
|
Sign up to set email alerts
|

Influence of childhood abuse and neglect subtypes on late-life suicide risk beyond depression

Abstract: The association of childhood maltreatment and suicide has been extensively examined within the population. Depression figures as a main cause for the elevated suicide rate in advanced ages and is often related to childhood maltreatment. The purpose of the present study was to examine the relationship between childhood maltreatment subtypes and suicide risk, testing geriatric depression as a moderator. This is a cross-sectional study looking at a sample of 449 individuals 60 year s old or older from the Multidi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
41
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(47 citation statements)
references
References 48 publications
5
41
0
1
Order By: Relevance
“…Childhood maltreatment is also associated with earlier age of first suicide attempt [51]. Additionally, an association between childhood maltreatment and suicide risk in 449 individuals 60 years of age or older was recently reported from the Multidimensional Study of the Elderly of Porto Alegre Family Health Strategy [52]. The effect was independent of geriatric depressive symptom severity.…”
Section: Childhood Maltreatment Increases Risk For Illness Severity Amentioning
confidence: 89%
See 1 more Smart Citation
“…Childhood maltreatment is also associated with earlier age of first suicide attempt [51]. Additionally, an association between childhood maltreatment and suicide risk in 449 individuals 60 years of age or older was recently reported from the Multidimensional Study of the Elderly of Porto Alegre Family Health Strategy [52]. The effect was independent of geriatric depressive symptom severity.…”
Section: Childhood Maltreatment Increases Risk For Illness Severity Amentioning
confidence: 89%
“…Several groups have sought to determine the impact of single types of childhood maltreatment on mood disorders. Although all types of childhood maltreatment (physical, emotional, and sexual) increase disease vulnerability and risk for more severe illness course in mood disorders, including increased risk for suicide [52], there may be some distinctions between individual subtypes and associated outcomes [70]. An association between sexual abuse and lifetime risk for anxiety disorders, depression, and suicide attempts independent of other types of maltreatment has been reported [2,71,72].…”
Section: Experiencing Single Subtypes Of Abuse and Neglect Vs Experimentioning
confidence: 99%
“…Child neglect, the omission of needed caregiving behaviors, is the most common form of maltreatment reported to authorities (U.S. Department of Health & Human Services, 2018), and is associated with at least as much harm as other forms of child abuse (Gilbert et al, 2009;Stoltenborgh, Bakermans-Kranenburg, & van IJzendoorn, 2013). Adverse impacts include substance abuse (Hussey, Chang, & Kotch, 2006), post-traumatic stress disorder (Widom, 1999), suicide risk (Behr Gomes Jardim et al, 2018), violent behavior (McGuigan, Luchette, & Atterholt, 2018), and developmental delays (Hildyard & Wolfe, 2002). Yet, neglect remains a less studied and understood form of maltreatment (Mennen, Kim, Sang, & Trickett, 2010;Stoltenborgh et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…However, the role of depressive symptoms in the association between childhood abuse and suicidality was not consistent in different studies. A study of elderly people over 60 years of age showed that the interaction terms of various types of childhood maltreatment and depression symptoms were not significantly related to suicide [22]. In addition, other studies have suggested that depression symptoms may play a mediating role in childhood abuse and suicidal behavior [28,50], but these studies did not rule out the association between the interaction terms of childhood abuse and depression symptoms, and suicidal behavior before the mediation analysis.…”
Section: Discussionmentioning
confidence: 96%
“…For example, a study analyzed the interaction between childhood abuse and mental disorders, and its impacts on suicidal behavior and found that childhood abuse had a significant impact on suicidal behavior in the general population but not on individuals with mood disorders [20]. However, another study showed that the interaction terms of various types of childhood maltreatment and depression symptoms were not significantly related to suicide [22]. Finally, few studies have explored the potential moderating role of depressive symptoms in the association between childhood abuse and suicidal behavior in Chinese adolescents.…”
Section: Introductionmentioning
confidence: 99%